The reliability of methicillin sensitivity tests on four culture media. Issue 5 (May 1974) - Brown, D. F. J.; Kothari, D.
Abstract : The influence of culture medium, incubation temperature, and antibiotic content on the reliability of methicillin disc-sensitivity tests on strains of Staphylococcus aureus was evaluated. Tests were performed with an inoculum giving semiconfluent growth of colonies on four media, with 5-μg and 10-μg methicillin discs at incubation temperatures of 30, 35, and 37°C. With Sensitest agar and Mueller-Hinton agar at 35°C or below, methicillin resistance was reliably detected. On DST agar and Wellcotest agar discrimination between sensitive and resistant strains was possible only at 30°C. On Wellcotest agar and DST agar it was not possible to detect methicillin resistance in one resistant strain at any temperature. For sensitive and resistant strains, the use of a 5-μg disc allowed greater differentiation than the 10-μg disc.